Neonatal invasive group B streptococcus infection, over a 10 year period, in West Hertfordshire, UK - Rodrigues, C; Parida, S; Narayanan, S (Allied Academies, 2017)
Introduction Group B Streptococcus (GBS) infection is the most important cause of neonatal infection in developed and developing countries. UK National guidance for the prevention of neonatal GBS infection was published in 2003 and updated in 2012. This surveillance study aimed to assess the burden of invasive neonatal GBS disease over a decade in a single UK county. Method A retrospective analysis was done of GBS positive cultures from blood and cerebrospinal fluid in babies aged 0-89 days, from 1 January, 2004 to 1 January, 2014. Notes were reviewed and a standard proforma completed by a clinician to identify patient demographics, clinical features, clinical course, treatment and outcome. Results There were 41 cases of GBS disease, with an overall incidence of 0.73 per 1000 live births and 17% (n=7) had GBS meningitis. Intrapartum antibiotic prophylaxis was given to 25% (n=4) of eligible mothers. Treatment was for appropriate duration, with exception for severe clinical features. The outcome of GBS meningitis was favourable, with 14% mortality. Conclusion The rates of early onset disease 0.44 per 1000, and late onset disease 0.28 per 1000 live births, are in keeping with other national studies of UK incidence. However, this trend is increasing and improvements are needed for better prevention of GBS disease.